Factors causing speaking anxiety faced by Indonesian students during teaching practices in the Philippines - Purbaya, Chrisna; Mulyadi; Puspita, Hilda (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2024)
This research aims to know factors causing speaking anxiety faced by Indonesian students doing teaching practice in Philippines and effects of that anxiety. This research applied semi- structure interview to 3 Indonesian students from SEA Teacher batch 8. Based on data, the factors of speaking anxiety were Language Skills, Students’ Background, Being Watched and Negative Evaluation from participants’ perception. Anxiety has affected to students such as avoiding talked with someone, having fear of miss understanding with students, furthermore improving English in speaking and doing demonstration before teaching English in a class are necessary.